Herbal formula xuling-jiangu improves bone metabolic balance in rats with ovariectomy-induced osteoporosis via the gut-bone axis - Chen, Juan; Ng, Szetuen; Xu, Pengchao; Chen, Sainan; Li, Shengqiang; Chen, Xuan; Xie, Lihua; Ge, Jirong (Frontiers in Pharmacology, 2024)
Introduction The XuLing JianGu recipe (XLJGR) is an empirical traditional Chinese medicine formula used for the treatment of osteoporosis. This study aims to explore the effects of XLJGR on the intestinal microbiota composition and endogenous metabolites in ovariectomized (OVX) rats. Methods An OVX rat model was established to evaluate the intervention effects of XLJGR. The measured indicators included bone density, serum bone metabolism markers, and an analysis of the types and abundances of intestinal microbiota, along with changes in endogenous metabolites. Additionally, MC3T3-E1 cells were used to validate the differential metabolites. Results XLJGR significantly reduced the abundance of Bacteroides, Butyricicoccus, and other bacterial strains in the gut. KEGG metabolic pathway enrichment analysis showed that XLJGR intervention led to notable changes in pathways such as peptidoglycan biosynthesis, carbapenem biosynthesis, and vancomycin resistance. Moreover, XLJGR significantly upregulated key intestinal microbiota metabolites, including gabapentin(GAB), camphoric acid(CAA), and nonanedioic acid(AZA), thereby promoting the proliferation and osteogenic differentiation of MC3T3-E1 cells. Discussion This study highlights the potential biomedical applications of XLJGR in promoting bone health by positively affecting intestinal microbiota and metabolic characteristics. These findings suggest that XLJGR may serve as a viable alternative in the treatment of osteoporosis, warranting further exploration of its therapeutic mechanisms and clinical applications.